Technical Note: Design of rockfall net fences and the new ETAG 027 European guideline - Peila, D.; Ronco, C. (Natural hazards and earth system sciences, 2009)
The need for protection against rockfall has led to the development of different types of technological solutions that are able to both prevent blocks from detaching from rock walls and to control, intercept or deviate the blocks during movement. Of the many devices that are able to intercept and stop a block, one of the most frequently used is net fence. Many different types of full-scale tests have been carried out, with different test site geometries and procedures to study their behaviour and to certify these devices. This has led to a series of data and information that are not easy to compare. The recent endorsement, by the European Organization for Technical Approvals (EOTA), of a European Technical Approval Guideline (ETAG), which defines how to test and assess the performance of a net fence, is therefore a great innovation that will change both the market and the design procedures of these devices. The most important innovations introduced by this new guideline are here presented and discussed and a net fence design procedure for protection against rockfall is provided.